Hubungan antara pengamatan kepada Pendidikan Islam dengan kepatuhan kepada peraturan dan disiplin sekolah - Khazain, Zakaria (2010)
Social ill and disciplinary problems among school students are becoming serious lately. It has become a topic of discussion for everyone. This problem has to be addressed wisely so that it leaves a good impact on students. We are accepted in the society when we have good discipline. In addition to that, religious knowledge is the basis for moulding the character of a Muslim. Practice is the action done based on the knowledge and experiences that one has. The combination of those elements produces a true Muslim. A study was carried out at secondary schools in the district of Tawau, Sabah so as to identify the relationship between appreciation of religious values and compliance to regulations and discipline in schools. The sample of this study was 617 secondary school students from four schools in the district of Tawau, Sabah. Random stratified sampling was used in this study. Questionnaires, consisting of respondents' profile, level of religious knowledge and the level of appreciation of religious values, were distributed. Data were collected and analyzed using SPSS version 12.0. The focus of this study was to see the level of understanding and appreciation of the content of Islamic Education among the students. This study also sought to identify the relationship between the understanding of Islamic Education and the compliance of students towards the school rules. Descriptive analysis method and Pearson Correlation test were used in this study. The findings indicated that respondents' understanding of religion was at the moderate level meanwhile the level of appreciation of religious values was low. On the other hand, findings from Pearson Correlation test showed that there was a significant relationship between the level of understanding of Islamic Education and the compliance of students towards the school rules. The relationship between both the variables was high and positive